1999
DOI: 10.1016/s1010-7940(98)00310-8
|View full text |Cite
|
Sign up to set email alerts
|

Arch and descending aortic aneurysms: influence of perfusion technique on neurological outcome1

Abstract: Anterograde perfusion using a proximal aortic cannula provides a low risk of cerebral embolism and allows extensive aortic resection with low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…To ensure TL perfusion after distal reconstruction, to minimize retrograde delivery of embolic material, and to minimize FL pressurization, there is an overwhelming consensus that orthograde corporeal perfusion via the aortic graft should be instituted if FemA cannulation has previously been used. Femoral cannulation is ill-advised in the presence of distal aortic atherosclerotic disease, because it risks proximal atheroembolization (172,173). In the context of ATAAD, initial FemA cannulation remains reasonable, provided malperfusion monitoring is applied and aortic imaging confirms an absence of atheroma.…”
Section: The Aims and Objectives Of Ataad Surgerymentioning
confidence: 99%
“…To ensure TL perfusion after distal reconstruction, to minimize retrograde delivery of embolic material, and to minimize FL pressurization, there is an overwhelming consensus that orthograde corporeal perfusion via the aortic graft should be instituted if FemA cannulation has previously been used. Femoral cannulation is ill-advised in the presence of distal aortic atherosclerotic disease, because it risks proximal atheroembolization (172,173). In the context of ATAAD, initial FemA cannulation remains reasonable, provided malperfusion monitoring is applied and aortic imaging confirms an absence of atheroma.…”
Section: The Aims and Objectives Of Ataad Surgerymentioning
confidence: 99%
“…Profound hypothermic circulatory arrest was the pioneering technique [1] and, later as an adjunct to it, retrograde cerebral perfusion, which is still in use by some have been the preferred procedures for successful aortic arch repair [2]. However, these techniques did not provide necessary safety as far as neurological results are concerned and had some additional deleterious effects due to extended cardiopulmonary bypass times for cooling and rewarming and subsequent disturbances related to deep hypothermia [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Provided that it is safe, ascending aorta cannulation may have a great advantage because of the technical simplicity, especially in the situations of hemodynamic instability. And prompt establishment of antegrade systemic perfusion may also be of benefit [14][15][16]. The obtained results indicated that this technique could be performed safely under ultrasound-guided Seldinger technique.…”
Section: Discussionmentioning
confidence: 99%